Effects of high pressure on the ferromagnetism and in-plane electrical transport of (Ba0.904K0.096)(Zn0.805Mn0.195)2As2 single crystal. (29th May 2018) - Zhao, G Q; Li, Z; Sun, F; Yuan, Z; Chen, B J; Yu, S; Peng, Y; Deng, Z; Wang, X C; Jin, C Q
Abstract: Pressure technique is an effective way to modify magnetic properties of diluted magnetic semiconductors (DMS). Based on single crystal, in-plane electrical transport properties of a new generation DMS (Ba0.904 K0.096 )(Zn0.805 Mn0.195 )2 As2 have been measured with hydrostatic pressure up to 1.8 GPa. Magnetic properties of the single crystal sample are effectively tuned by pressure. Upon compression, the in-plane resistivity initially decreases but then increases when pressure is higher than 1.2 GPa. First principle calculations suggest that decrease of the resistivity is due to enhancement of density of state at Femi energy while increase of the resistivity under higher pressure is caused by distorted MnAs4 tetrahedra. We reveal that the configuration of the MnAs4 tetrahedra and strength of interlayer As–As bonding are of importance to ferromagnetic coupling of (Ba, K)(Zn, Mn)2 As2 .